Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1242/jcs.00692
|View full text |Cite
|
Sign up to set email alerts
|

Architectural defects in pronuclei of mouse nuclear transplant embryos

Abstract: Reprogramming somatic nuclear function by transplantation of nuclei into recipient oocytes is associated with a morphological remodeling of the somatic nucleus. Successful cloning of animals by nuclear transplantation (NT) demonstrates that reprogramming somatic cell function is possible. However, low pregnancy rates and high frequencies of lethal abnormalities in animals born suggest that reprogramming is rarely complete. To address this issue, we tested the hypothesis that nuclear transplantation leads to nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Down-regulation of these three genes in the present study indicated that translation failure occurred in cloned embryos. In addition, some genes related to chromatin organization and cell cycle regulation, rcc1 and smc1a were down-regulated in the cloned embryos, in agreement with a previous study in somatic cell NT embryos [37][38][39]. Some other genes related to the regulation of cell cycle were also differentially expressed in the cloned embryos, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Down-regulation of these three genes in the present study indicated that translation failure occurred in cloned embryos. In addition, some genes related to chromatin organization and cell cycle regulation, rcc1 and smc1a were down-regulated in the cloned embryos, in agreement with a previous study in somatic cell NT embryos [37][38][39]. Some other genes related to the regulation of cell cycle were also differentially expressed in the cloned embryos, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the reports that most NT embryos cease development at the pre-and peri-implantation stages [1,41], it is probable that the accumulation of different abnormalities observed in NT embryos at various developmental stages, such as failure to erase some of the features of donor cells [42][43][44], abnormal gene expression [4,8,10,25,[45][46][47], abnormal DNA methylation [4][5][6], abnormal formation of placentae [1,41,[48][49][50], and the abnormalities detected in this study, leads to gradual loss of NT embryos. Abnormalities that have not been detected in previous studies and/or small differences in gene expression may seriously affect embryonic development.…”
Section: Discussionmentioning
confidence: 72%
“…After removal of cycloheximide 6 h following NT, extensive translation and expression of NuMA could occur. Consistently, NuMA reassembles as a result of translation from maternal mRNA and of de novo transcription from transplanted nuclear genomes in the mouse cloning (Moreira et al 2003). NuMA could be important for spindle pole organization in primates (Simerly et al 2003).…”
Section: Functions Of Numa In Reprogramming and Cell Replicationmentioning
confidence: 82%
“…NuMA was also was detected in pronuclear stage embryos of mouse clones and in donor cumulus cells (Moreira et al 2003), as well as in normal bovine embryos (Degrouard et al 2004). In bovine clones produced by simultaneous fusion and activation, NuMA was weak or absent in donor nuclei, but strongly expressed in pronuclei following NT.…”
Section: Functions Of Numa In Reprogramming and Cell Replicationmentioning
confidence: 91%